State-of-the-Art Management of Patients Suffering from Chronic Lymphocytic Leukemia. - Clifford, R; Schuh, A (Libertas Academica Ltd., 2012)
The management of chronic lymphocytic leukemia (CLL) has evolved dramatically in the last decade. For the first time, clinical intervention has been shown to alter the natural history of the disease. Considerable efforts are focussing on better patient selection and response prediction, and it is expected that the publication of the first 200 CLL genomes will spark new insights into risk stratification of CLL patients. Besides, many new agents are being evaluated on their own and in combination therapy in early and late Phase clinical studies. Here, we provide a general clinical introduction into CLL including diagnosis and prognostic markers followed by a summary of the current state-of-the-art treatment. We point to areas of continued clinical research in particular for patients with co-morbidities and highlight the challenges in managing refractory disease.